Erasmus’ Heritage - Frijhoff, Willem (Erasmus studies, 2015)
The ironic but very readable dialogues on folk religion in Erasmus’ Colloquia were used as school books for two centuries. Though their influence on the battle against superstition is difficult to measure, they obviously reflect the practices and debates of their own time. This article confronts Erasmus’ dialogue on exorcism with the ideas and practices of folk religion in the sixteenth-century biconfessional duchy of Cleves under Duke William V. Two sources stand out in particular: the influential treatise De praestigiis daemonum (1563) of court physician Johan Wier, an admirer of Erasmus and opponent of magic and sorcery, and the vernacular treatise on magical agency by Jacob Vallick, Catholic parish priest of the village of Groessen, which was printed by Nicolaas Biestkens in 1559. Vallick’s practical and pastoral approach to these matters, though it greatly irritated Wier, nevertheless reflects the influence of Erasmianism in Cleves even among the lower clergy.